IMPLEMENTASI KEBIJAKAN PENETAPAN TARIF KAMAR PADA HOTEL ARYADUTA PEKANBARU - Artika Safilarani; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to find out and analyze how the policy of determining the room rate applied to the Hotel Aryaduta Pekanbaru.The method of this research is using kualitatif analysis method. Analysis in the research based in literature, observation, and direct interview with informan who consider able to provide informationrelation to problem examined.Room occupancy is increasing but income is not in accordance with the target revenue that has been set, therefore management need to consider and fix back the policy of setting room rate which have been applied at Hotel Aryaduta Pekanbaru.Keywords : Implementation, Room Rate Policy